Tyrosol and its metabolites as antioxidative and anti-inflammatory molecules in human endothelial cells. Issue 8 (25th July 2017) - Muriana, Francisco J. G.; Montserrat-de la Paz, Sergio; Lucas, Ricardo; Bermudez, Beatriz; Jaramillo, Sara; Morales, Juan C.; Abia, Rocio; Lopez, Sergio
Abstract : Novel biological activities for tyrosol metabolites on human endothelial cells. Abstract : Tyrosol (Tyr) is a phenolic compound found in virgin olive oil. After ingestion, Tyr undergoes extensive first pass intestinal/hepatic metabolism. However, knowledge about the biological effects of Tyr metabolites is scarce. We chemically synthesized Tyr glucuronate (Tyr-GLU) and sulphate (Tyr-SUL) metabolites and explored their properties against oxidative stress and inflammation in TNF-α-treated human umbilical vein endothelial cells (hECs). Tyr and Tyr-SUL prevented the rise of reactive oxygen species, the depletion of glutathione, and the down-regulation of glutathione peroxidase 1, glutamate-cysteine ligase catalytic subunit, and heme oxygenase-1 genes. Tyr-SUL and to a lower extent Tyr and Tyr-GLU prevented the phosphorylation of NF-κB signaling proteins. Tyr-GLU and Tyr-SUL also prevented the over-expression of adhesion molecules at gene, protein, and secretory levels, and the adhesion (Tyr-SUL > Tyr-GLU) of human monocytes to hECs. In vivo, Tyr, and most notably Tyr-SUL in a dose-dependent manner, ameliorated plantar and ear edemas in mice models of acute and chronic inflammation. This study demonstrates the antioxidant and/or anti-inflammatory properties of Tyr metabolites, with Tyr-SUL being the most effective.